Mild cognitive impairment: a history and the state of current diagnostic criteria. (5th November 2014) - Gerstenecker, Adam; Mast, Benjamin
ABSTRACT: Background: Mild cognitive impairment (MCI) is a diagnostic classification used to describe patients experiencing cognitive decline but without a corresponding impairment in daily functioning. Over the years, MCI diagnostic criteria have undergone major changes that correspond to advancements in research. Despite these advancements, current diagnostic criteria for MCI contain issues that are reflected in the research literature. Methods: A review of the available MCI literature was conducted with emphasis given to tracing MCI from its conceptual underpinnings to the most current diagnostic criteria. A clinical vignette is utilized to highlight some of the limitations of current MCI diagnostic criteria. Results: Issues are encountered when applying MCI diagnostic criteria due to poor standardization. Estimates of prevalence, incidence, and rates of conversion from MCI to dementia reflect these issues. Conclusions: MCI diagnostic criteria are in need of greater standardization. Recommendations for future research are provided that could potentially bring more uniformity to the diagnostic criteria for MCI and, therefore, more consistency to the research literature.